Work and health in Latin America: results from the working conditions surveys of Colombia, Argentina, Chile, Central America and Uruguay. Issue 6 (16th January 2017) - Merino-Salazar, Pamela; Artazcoz, Lucía; Cornelio, Cecilia; Iñiguez, María José Itatí; Rojas, Marianela; Martínez-Iñigo, David; Vives, Alejandra; Funcasta, Lorena; Benavides, Fernando G
Abstract : Objective: To describe working and employment conditions, and health status between non-agricultural employees with a written contract from Colombia, Argentina, Chile, Central America and Uruguay. Methods: We compared data from the first working condition surveys (WCS) of Colombia, Argentina, Chile, Central America and Uruguay. For comparative purposes, we selected a subsample of 15 241 non-agricultural employees aged 18–64 years and working with a written contract. We calculated prevalences and 95% CIs for the selected variables on working and employment conditions, and health status, separated by sex. Results: Across all countries, at least 40% of women and 58% of men worked >40 hours a week. The most prevalent exposures were repetitive movements, followed by noise and manual handling, especially among men. Psychosocial exposures were very common among both sexes. Workers in Chile (33.4% of women and 16.6% of men) and Central America (24.3% of women and 19.1% of men) were more likely to report poor self-perceived health and were least likely to do so in Colombia (5.5% of women and 4.2% of men). The percentage of workers reporting occupational injuries was <10% across all countries. Conclusions: This study provides, for the first time, a broad picture of work and health in different Latin American countries, based on the national WCSs available. This allows for a better understanding of occupational health and could serve as a baseline for future research and surveillance of work and health in the Region. However, greater efforts are needed to improve WCSs comparability.